Designing Governance Structures for Performance and Accountability Developments in Australia and Greater China - Podger, Andrew; Su, Tsai-tsu; Wanna, John; Chan, Hon S.; Niu, Meili (ANU Press, 2020)
Designing Governance Structures for Performance and Accountability discusses how formal and informal governance structures in Australia, the People's Republic of China (PRC) and Taiwan may be designed to promote performance and to ensure accountability. The book presents a selection of papers developed from the Greater China Australia Dialogue on Public Administration's seventh workshop held in June 2017 hosted by City University of Hong Kong. Insights are provided on both current developments in the different contexts of the three jurisdictions examined, and on broader institutional and organisational theories. Chapters cover theories of organisational forms and functions in public administration, the 'core' agency structures used in the different jurisdictions, the structures used to deliver public services (including non-government organisational arrangements) and other 'non-core' agency structures such as government business enterprises, regulatory organisations and 'integrity' organisations. A particular emphasis is placed on the institutional arrangements the executive arm of government uses for advising on and implementing government policies and programs. Although the book explores arrangements and developments within very different political governance systems, the purposes of the structures are similar: to promote performance and accountability. This book is a companion volume to Value for Money: Budget and Financial Management Reform in the People's Republic of China, Taiwan and Australia (ANU Press, 2018).